Effects of Unloading Rate on Energy Evolution Mechanism in the Single-Side Unloading Failure of Highly Stressed Marble. (9th April 2020) - Xu, Wensong; Zhao, Guangming; Meng, Xiangrui; Kao, Siming; Huang, Shunjie; Liu, Chongyan
Abstract : Highly stressed rock masses continuously exchange substances and energy with the outer environment during single-side unloading, which is a damage evolution process with energy dissipation. The true triaxial unloading disturbance rock test system was utilized to perform single-side unloading tests of marble specimens at different unloading rates and axial pressures. The unloading failure characteristics of the marble specimens were revealed from the perspective of energy conversion. Results indicated the following: (1) The marble specimen was more likely to be damaged under the single-side unloading condition than under the loading condition, with the unloading failure strength reaching 80% of the loading failure strength. (2) Crack propagation under single-side unloading was intermittent. (3) A high single-side unloading rate corresponded to a high release rate of the energy concentrated inside the rock mass, a small amount of energy dissipated due to second failure, insufficient crack propagation, and occurrence of only tensile failure. (4) A large amount of axial strain energy indicated a great amount of energy aggregated inside the rock mass and the generation of tensile stress due to unloading dilatancy. Consequently, a high critical value for splitting the failure of the rock specimen implied large failure-induced energy dissipation and a high failure degree. The study of failure energy evolution mechanism in the single-side unloading of highly stressed rock masses at different unloading rates will provide great guiding significance in controlling underground engineering disasters and guaranteeing construction safety.